BENTUK KOMUNIKASI BIMBINGAN PERKAWINAN (BINWIN) TERHADAP CALON PENGANTIN - Wahyu Ziaulhaq (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2022)
This study seeks to describe the form of communication of marriage guidance to prospective brides, the purpose of this research is to educate readers and organizers of marriage guidance to conduct a thorough evaluation so that in the future the implementation of marriage guidance can be carried out optimally. This type of research is a qualitative research that seeks to describe social phenomena that are developing in the current mass and then described scientifically by following the applicable research principles. From the results of this study, it was found that the implementation of marriage counseling was carried out for two days, the budget for marriage guidance activities was obtained from the Non-Tax State Revenue for Marriage and Referral fees, the resource persons came from the District KUA and health workers from the District Health Center who have competence in the field of sakinah family and reproductive health. The obstacle is that the implementation of guidance held for two days is considered insufficient, the budget for implementing marriage guidance is limited. The minimum number of participants attending marriage counseling.